Tetramethylpyrazine alleviates cerebral ischemia-reperfusion injury via NRF2/HO-1/GPX4-mediated ferroptosis inhibition - Hengpei Gong; Yinjun Lu; Lingfeng Wang; Xueyuan Gong; Jingfang Zhao; Zhenxin Li (Tissue and Cell, 2027)

Millennial cold–dry events during marine isotope stage 11a based on sedimentary records from the Heqing Basin and their global climatic dynamical responses - Guohui Liu; Xinwen Xu; Shenghui Wang; Lirong Hou; Yuqing Zhang; Liu Yang; Jingfang Zhang; Yuzhu Zhang; Hui Zhao; Chaofeng Fu; Xiaoke Qiang; Wen Liu; et al. (Global and Planetary Change, 2026)

Liraglutide affects mitochondrial function and histone acetylation through the NQO1/SIRT3 pathway in diabetic kidney disease - Jie Gao; Xiaoyu Lv; Pingping Zhao; Bingjing Pan; Jingfang Liu (Molecular and Cellular Biochemistry, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Long-term capsaicin intake and gut inflammation: microbial alterations, metabolic mechanisms, and intervention effects - Liangliang Zhu; Yijia Chen; Jiayang Jin; Mengyao Zhao; Jingfang Ran; Hao Yin; Xiaoguo Ji; Liming Zhao (Food Research International, 2026)

Lanthanide-polyoxometalate-based anti-swelling luminescent conductive organohydrogel for information encryption and underwater sensing - Xinyu Lu; Jingfang Li; Min Gao; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

Multifunctional conductive luminescent hydrogel with low-temperature enhanced mechanical properties: Applications in sensing, gas detection, and information encryption - Min Gao; Jingfang Li; Yumei Hua; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2026)

Cross-scale long-term spatiotemporal dynamics and influencing indicators of summer urban heat risk in mega-urban agglomeration - Jiachen Liu; Xiaofang Wang; Jingfang Yan; Xinfei Zhao; Wenke Chen; Le Yin; Baolei Zhang (Journal of Cleaner Production, 2025)

Mitofusin 2 Mediates the Protective Effect of NR6A1 Silencing Against Neuronal Injury in Experimental Stroke Models - Bingtian Xu; Zhuhe Liu; Kechun Chen; Qian Zhao; Haixia Wen; Jingfang Lin; Jiangping Xu; Haitao Wang; Honghao Wang; Yuanyuan Wang (Molecular Neurobiology, 2025)

Acetylcholinesterase-free colorimetric sensing platform for carbosulfan detection based on hollow PDA/MnO2 nanozyme - Jingfang Guo; Feng Zhao; Zhenhui Yue; Zhen Lei (Food Chemistry, 2025)

Oxymatrine reduces hepatic lipid synthesis in rat model of nonalcoholic steatohepatitis by regulating Sirt1/AMPK and LXR/Plin2/SREBP-1c pathways - Jingfang Xiong; Gaofeng Chen; Ying He; Changqing Zhao; Dongya Chen; Yihui Liu; Zhaolin Zhang; Yijun Wu; Hong Xu (Chemico-Biological Interactions, 2025)

Multi-stimuli-responsive conductive and luminescent hydrogels for wearable sensors and information encryption transmission - Min Gao; Jingfang Li; Sicong Zhao; Guangming Li (Chemical Engineering Journal, 2024)

SIRT3: A Potential Target of Different Types of Osteoporosis - Binjing Pan; Chongyang Chen; Yangting Zhao; Jing Cai; Songbo Fu; Jingfang Liu (Cell Biochemistry and Biophysics, 2024)

Enhanced AGS by granular activated carbon loaded with nano iron when treating low strength and low COD/TN ratio municipal wastewater: Microbial metabolism, electron transfer and enhancement mechanism - Lei Peng; Haibo Li; Jianbo Guo; Jingfang Lu; Yanan Hou; Yi Han; Daohong Zhang; Yuanyuan Song; Jianhai Zhao (Journal of Environmental Chemical Engineering, 2024)

Genome-wide association mapping combined with gene-based haplotype analysis identify a novel gene for shoot length in rice (Oryza sativa L.) - Tifeng Yang; Jingfang Dong; Junliang Zhao; Longting Zhang; Lian Zhou; Wu Yang; Yamei Ma; Jian Wang; Hua Fu; Jiansong Chen; Wenhui Li; Haifei Hu; et al. (Theoretical and Applied Genetics, 2023)
Key message Genome-wide association mapping revealed a novel QTL for shoot length across multiple environments. Its causal gene, LOC_Os01g68500 , was identified firstly through gene-based haplotype analysis, gene expression and knockout transgenic verification. Abstract Strong seedling vigor is an important breeding target for rice varieties used in direct seeding. Shoot length (SL) is one of the important traits associated with seedling vigor characterized by rapid growth of seedling, which enhance seedling emergence. Therefore, mining genes for SL and conducting molecular breeding help to develop varieties for direct seeding. However, few QTLs for SL have been fine mapped or cloned so far. In this study, a genome-wide association study of SL was performed in a diverse rice collection consisting of 391 accessions in two years, using phenotypes generated by different cultivation methods according to the production practice, and a total of twenty-four QTLs for SL were identified. Among them, the novel QTL qSL-1f on chromosome 1 could be stably detected across all three cultivation methods in the whole population and indica subpopulation. Through gene-based haplotype analysis of the annotated genes within the putative region of qSL-1f , and validated by gene expression and knockout transgenic experiments, LOC_Os01g68500 (i.e., Os01g0913100 in RAP-DB) was identified as the causal gene for SL, which has a single-base variation (C-to-A transversion) in its CDS region, resulting in the significant difference in SL of rice. LOC_Os01g68500 encodes a DUF538 (Domain of unknown function) containing protein, and the function of DUF538 protein gene on rice seedling growth is firstly reported in this study. These results provide a new clue for exploring the molecular mechanism regulating SL, and promising gene source for the molecular breeding in rice.

Vegetation restoration enhances soil erosion resistance through decreasing the net repulsive force between soil particles - Rentian Ma; Feinan Hu; Chenyang Xu; Jingfang Liu; Zhenghong Yu; Gang Liu; Shiwei Zhao; Fenli Zheng (CATENA, 2023)

Evaluation of novel isolates of Lacticaseibacillus rhamnosus Probio-M9 derived through space mutagenesis - Jingfang Yang; Yue Sun; Xueyan Lei; Lixia Zhao; Rui Luo; Wenjun Liu (Food Bioscience, 2023)

Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY - Zhe Wang; Xu Duan; Guangyue Ren; Jingfang Guo; Jiangtao Ji; Yiming Xu; Weiwei Cao; Linlin Li; Mengyue Zhao; Yuan Ang; Xin Jin; Bhesh Bhandari; et al. (Food Chemistry, 2023)

The crosstalk between the Notch, Wnt, and SHH signaling pathways in regulating the proliferation and regeneration of sensory progenitor cells in the mouse cochlea - Jingfang Wu; Wen Li; Luo Guo; Liping Zhao; Shan Sun; Huawei Li (Cell and Tissue Research, 2021)
Sensory hair cells (HCs) are highly susceptible to damage by noise, ototoxic drugs, and aging. Although HCs cannot be spontaneously regenerated in adult mammals, previous studies have shown that signaling pathways are involved in HC regeneration in the damaged mouse cochlea. Here, we used a Notch antagonist (DAPT), a Wnt agonist (QS11), and recombinant Sonic hedgehog (SHH) protein to investigate their concerted actions underlying HC regeneration in the mouse cochlea after neomycin-induced damage both in vivo and in vitro. With DAPT, the numbers of HCs increased, and supporting cell (SC) proliferation was seen in both the intact and damaged cochlear sensory epithelia, while these numbers were unchanged in the presence of QS11. When simultaneously treated with DAPT and QS11, the number of HCs increased dramatically, and much greater SC proliferation was seen in the cochlear epithelium. In transgenic mice with both Notch1 conditional knockout and β-catenin over-expression, cochlear SC proliferation and HC regeneration were more obvious than in either Notch1 knockout or β-catenin over-expressing mice separately. When cochleae were treated with DAPT, QS11, and SHH together, SC proliferation was even greater, and this proliferation was seen in both the HC region and the greater epithelial ridge. High-throughput RNA sequencing was used to identify the differentially expressed genes between all groups, and the results showed that the SHH and Wnt signaling pathways are involved in SC proliferation. Our study suggests that co-regulation of the Notch, Wnt, and SHH signaling pathways promotes extensive cell proliferation and regeneration in the mouse cochlea.

Evaluating the effect of soil internal forces on the stability of natural soil aggregates during vegetation restoration - Rentian Ma; Feinan Hu; Jingfang Liu; Shiwei Zhao (Journal of Soils and Sediments, 2021)

NAC transcription factor ONAC066 positively regulates disease resistance by suppressing the ABA signaling pathway in rice - Qing Liu; Shijuan Yan; Wenjie Huang; Jianyuan Yang; Jingfang Dong; Shaohong Zhang; Junliang Zhao; Tifeng Yang; Xingxue Mao; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2018)

Purification and antibacterial mechanism of fish-borne bacteriocin and its application in shrimp (Penaeus vannamei) for inhibiting Vibrio parahaemolyticus - Xinran Lv; Jingfang Du; Yu Jie; Bolin Zhang; Fengling Bai; Hongfei Zhao; Jianrong Li (World Journal of Microbiology and Biotechnology, 2017)

The germin-like protein OsGLP2-1 enhances resistance to fungal blast and bacterial blight in rice - Qing Liu; Jianyuan Yang; Shijuan Yan; Shaohong Zhang; Junliang Zhao; Wenjuan Wang; Tifeng Yang; Xiaofei Wang; Xingxue Mao; Jingfang Dong; Xiaoyuan Zhu; Bin Liu (Plant Molecular Biology, 2016)

Construction and characterization of the interdomain chimeras using Cry11Aa and Cry11Ba from Bacillus thuringiensis and identification of a possible novel toxic chimera - Yunjun Sun; Qiang Zhao; Dasheng Zheng; Xuezhi Ding; Jingfang Wang; Quanfang Hu; Zhiming Yuan; Hyun-Woo Park; Liqiu Xia (Biotechnology Letters, 2014)